Catastrophic expenditure associated with childhood hospitalisation for acute illness in Kenya and Uganda: a cross-sectional study - Sassy Molyneux; Johnstone Thitiri; Laura Mwalekwa; Molline Timbwa; Anna Vassall; Kirkby D Tickell; Judd L Walson; James Berkley; John Mukisa; Ezekiel Mupere; Peter Olupot-Olupot; Priya Sukhtankar; et al. (BMJ Public Health)
Introduction Childhood illness and hospitalisation result in both direct and indirect costs to families before, during and after admission. We aimed to estimate the catastrophic expenditure during hospitalisation for children with acute illness.Methods This was a prespecified cross-sectional substudy nested within two prospective studies. Participants were recruited and interviewed from three rural and three urban hospitals in Kenya and Uganda. A costing questionnaire was administered to the caregivers of 731 children hospitalised for acute illness to evaluate direct and indirect costs incurred by caregivers and families. Costs incurred were compared for families with children both with and without complicated severe malnutrition (CSM). Catastrophic out-of-pocket expenditure exceeding 10% and 25% of monthly income was assessed.Results The median (IQR) total cost during hospitalisation per child was US$47 (US$24–US$84), with higher costs for children with CSM, especially during hospitalisation (US$56 (US$26–US$99) vs US$36 (US$20–US$65); p<0.001). During hospitalisation, bed charges followed by food were the main cost drivers. Caregivers reported losing a median of 7 (4–11) days of productive time during a child’s hospitalisation with a mean loss of income of US$10 (SD US$25.6, median US$0 (US$0–US$10)). 92% and 74% of households experienced catastrophic expenditure at thresholds of 10% and 25% of monthly income, respectively. Caregivers reported borrowing, selling property and withdrawing other children from school to cope with costs.Conclusions Despite intentions of free healthcare services for under 5, families of acutely ill children very commonly faced catastrophic expenditure, especially for children with CSM. Interventions aimed at supporting financial protection, reducing additional healthcare costs, and lowering health service charges may help prevent catastrophic expenditures.